Complementary roles of domestic and international networks in sustaining internationalization of SMEs: a modeling approach - Karage, Ahmed Ibrahim; Raja Yusof, Raja Nerina; Nadarajah, Devika; Abdul, Mohani (Human Resource Management Academic Research Society, 2019)
The importance of networks in internationalization has been acknowledged in literature with much emphasis on international networks. What remains unclear is the complimentary role being played by domestic and international networks in entry and sustaining international market. This paper provides an empirical understanding of the joint influence of firm’s domestic network and international network in sustaining internationalization of SMEs in Sub Sahara African countries. The study also examined the role of international entrepreneurial orientation (IEO) in mediating the relationships between domestic network, international network and internationalization of SMEs. The objectives of the study were achieved by developing hypotheses relating to the network resources in domestic and international markets and internationalization of SMEs. Using partial least square (PLS), the study analyzed data from a sample of 266 exporting SMEs in Nigeria and shows that establishing and maintaining domestic and international networks are crucial in sustaining internationalization of SMEs. Furthermore, mediation effect of IEO was significant in the relationships. The study proposes that enhancing the capacity of exporting SMEs in IEO can further increase their capacity develop and sustain their network resources both at home and in international market.